2018
DOI: 10.1111/odi.12992
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of medication‐related osteonecrosis of the upper jaw: Case series

Abstract: Purpose The management of maxillary medication‐related osteonecrosis of the jaw (MRONJ) is challenging. Therefore, identifying the proper treatment is important. This study aimed to evaluate the surgical treatment of maxillary MRONJ using single‐layer closure with mucoperiosteal flap and double‐layer closure with buccal fat pad flap (BFPF) and mucoperiosteal flap and to find the outcomes after rehabilitation with obturators. Methods A retrospective analysis was conducted and included all surgically treated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 48 publications
1
37
0
12
Order By: Relevance
“…However, there is an increasing body of evidence suggesting that surgical removal of necrotic bone might be curative in patients with all MRONJ stages (Aljohani et al, 2019;Otto et al, 2018;Ristow et al, 2018), where cure is defined as long-term resolution of symptoms and complete mucosal closure (absence of residual bone exposure). Other studies have documented high success rate of surgical treatment compared to non-surgical treatment (Aljohani et al, 2019;Hauer et al, 2019;Yamada et al, 2018).…”
Section: Controver S Ie S On Manag Ement/ Tre Atmentmentioning
confidence: 99%
“…However, there is an increasing body of evidence suggesting that surgical removal of necrotic bone might be curative in patients with all MRONJ stages (Aljohani et al, 2019;Otto et al, 2018;Ristow et al, 2018), where cure is defined as long-term resolution of symptoms and complete mucosal closure (absence of residual bone exposure). Other studies have documented high success rate of surgical treatment compared to non-surgical treatment (Aljohani et al, 2019;Hauer et al, 2019;Yamada et al, 2018).…”
Section: Controver S Ie S On Manag Ement/ Tre Atmentmentioning
confidence: 99%
“…In 10 patients, treated with sequestrectomy (local resection) healing occurred in 5 (50%) and in 40 patients treated with block resection, 31 patients healed (77.5%). Our success rate for patients treated with block surgery is in accordance with other studies (Aljohani et al, 2018;. The results are further strengthened by Favia et al who in a recent publication concluded that MRONJ occurring both in neoplastic and non-neoplastic patients benefits more from a surgical treatment approach, whenever deemed possible, as non-surgical treatments do not seem to allow complete healing of the lesions (Favia et al, 2018).…”
Section: Risk Factorssupporting
confidence: 88%
“…When obtaining success rates in surgical treatment of MRONJ lesions in both cancer patients and osteoporotic patients as high as those in study III and similar studies (Aljohani et al, 2018;, much depends on the surgeon's skill and expertise (Ristow et al, 2015). A major challenge of surgical treatment is to distinguish the demarcation between viable and necrotic bone so that a minimum amount of bone is removed.…”
Section: Risk Factorsmentioning
confidence: 98%
“…In many cases, surgical treatment of stage III MRONJ patients leads to oroantral communication in the posterior maxilla. The closure of these defects represents an additional challenge to the oral surgeon and is essential to improve the long‐term life quality [ 13 ].…”
Section: Discussionmentioning
confidence: 99%